PENTINGNYA PERENCANAAN KEUANGAN SYARIAH DALAM UPAYA MENSEJAHTERAKAN EKONOMI KELUARGA DI DESA PANTAI SEDERHANA - Emy Syariah; Akmal Rizki Gunawan; Tatang Iskandar (An-Nizam, 2023)
Family financial planning in Indonesian society, the majority of which still use traditional concepts in rural areas, especially housewives who are now family financial managers, use funds that are only focused on consumption activities. The lack of public knowledge of sharia-based family financial planning in managing finances for families is still underestimated because they have not paid much attention to the importance of sharia-based financial planning. The implementation of this community service the author uses in the form of community education, namely by providing socialization in order to increase understanding of the people of Pantai Sederhana Village, Muara Gembong District. Implementation of socialization activities that have been held on Thursday, March 9, 2023 at the Simple Beach Village office face-to-face. The socialization began with the provision of material "The Importance of Islamic Financial Planning in Efforts to Prosper the Family Economy". Based on the conclusions above, participants can appreciate the importance of implementing Islamic finance in order to create prosperous financial conditions in the family. The suggestions recommended for further service or the community are to be able to practice directly in the form of training in several sessions to improve the ability to implement prosperous family financial planning to the community.